Need for disease resistance breeding against Corynespora cassiicola in crops - Sierra-Orozco, Edgar; Sandoya, German; Lee, Seonghee; Vallad, Gary; Hutton, Samuel (Frontiers in Agronomy, 2023)
Corynespora cassiicola (Cc) is a genetically diverse ascomycete found worldwide in tropical and subtropical regions. Cc causes necrotrophic diseases in several plant species, including important crops such as rubber tree, tomato, cotton, and cucumber. Evidence suggests the involvement of one or more Cc host-specific toxins in disease progression. Management of Cc crop diseases is based mainly on pesticide sprays. However, the pathogen's development of resistance to commonly used fungicides is documented. Resistance breeding is an attractive alternative or supplement to chemical control of Cc crop diseases, but research on this topic is very limited. This review describes the current plant resistance breeding efforts towards Cc resistance and discusses the potential influence of host-specific toxins (HSTs) on such efforts. Although some reports of host resistance exist in a few crops, resistant germplasm and knowledge about resistance mechanisms are limited. Some studies have suggested the involvement of HSTs in disease development, including the upregulation of resistance-related proteins in susceptible reactions and the recessive nature of resistance. In light of this, host resistance may not be achieved through commonly used dominant R-genes.